2011
DOI: 10.1111/j.1758-5872.2011.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Dementia in Chinese populations: Current data and future research

Abstract: This review summarizes the literature on the prevalence and incidence rates of dementia in Chinese populations, including survey results outside mainland China. We identified 15 prevalence studies and five incidence studies. The studies consistently reported sharply increased prevalence and incidence rates of dementia with increasing age. As estimated, there are at least 6,464,040 dementia patients in mainland China alone and we expect the number to rise in the coming decades. It is clear that dementia will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Promising results have been reported from a small scale clinical trial that used a specific type of mushroom (Yamabushitake) as the intervention [4]; however, more data are needed before a definitive conclusion can be drawn. We are aware that effective prevention may require multiple nutritional changes (for examples: homocysteinelowering B vitamins [24,25], tea and tea compounds [26,27], etc.) to achieve public health impact, but as a necessary first step the efficacy of each of the promising candidate should be assessed separately [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results have been reported from a small scale clinical trial that used a specific type of mushroom (Yamabushitake) as the intervention [4]; however, more data are needed before a definitive conclusion can be drawn. We are aware that effective prevention may require multiple nutritional changes (for examples: homocysteinelowering B vitamins [24,25], tea and tea compounds [26,27], etc.) to achieve public health impact, but as a necessary first step the efficacy of each of the promising candidate should be assessed separately [27].…”
Section: Discussionmentioning
confidence: 99%
“…We are aware that effective prevention may require multiple nutritional changes (for examples: homocysteinelowering B vitamins [24,25], tea and tea compounds [26,27], etc.) to achieve public health impact, but as a necessary first step the efficacy of each of the promising candidate should be assessed separately [27]. Mushrooms or active ingredients from mushrooms, such as ET, represent potential interventions.…”
Section: Discussionmentioning
confidence: 99%
“…We are also unable to determine the specific relationship between tea drinking and dementia risk. Given the rising tide of elderly persons with dementia in the coming decades (26) and the promising potential of tea drinking as a simple and cheap preventive measure, future cohort study with dementia incidence as the primary outcome is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies found that the conversion rate from cognitive impairment to dementia ranged from 10% to 40% per year . Further, it may take at least 10 years from the start of dementia pathology before any clinically detectable symptoms appear . Therefore, early detection of and intervention in cognitive impairment are essential to delaying conversion to dementia—and to reduce the suffering faced by patients and the burden on families and society.…”
Section: Introductionmentioning
confidence: 99%